Changes in the Sector Employment Structure of the Silesian Voivodeship beetwen 2009-2017 - Kotlorz, Dorota; Jarus, Oskar (Olsztyn Economic Journal, 2020)
Transformations of employment structures reflect changes in the economic structure. This structure is closely related to economic development. The importance and complexity of this field make structural changes one of the most important areas of scientific research. Detailed recognition and deepening of knowledge about sectoral transformations of employment structures, as well as current and future trends in this area, are necessary for finding optimal solutions that will accelerate changes in the economy. The purpose of the study is to identify and evaluate changes in the sectoral employment structure in the Silesian Voivodeship in the years 2009-2017, with particular emphasis on intra-sectoral changes in the service sector. In connection with this, an analysis of structural changes was carried out in the Silesian Voivodeship in the examined period. The research was based on data obtained from the Local Data Bank. The analysis of structural changes in employment was conducted using structure and dynamics indicators as well as one of the known measures of structure diversity. The results of the analysis allowed this study to recognize and assess changes within the sectoral employment structure within the studied region.